Long-term nutritional management of an obese German Spitz with paroxysmal dyskinesia, calcium oxalate urolithiasis, and suspected pancreatitis—A case report - Baptista da Silva, Camila; Hermans, Michelle; Ruiz-Suárez, Norberto; Verdoodt, Fien; Bhatti, Sofie Fatima Mareyam; Hesta, Myriam (Frontiers in Veterinary Science, 2023)
Background To our knowledge, this is the first description of long-term nutritional management in a dog with paroxysmal dyskinesia. Case summary An obese 9-year-old, male entire, German Spitz was presented for dietary management after being diagnosed with calcium oxalate urolithiasis and suspected pancreatitis. Since he was seven years old, the dog has had a history of neurological signs, which were thought to be epileptic seizures. He was treated with phenobarbital and potassium bromide and was clinically controlled. For his nutritional advice, aiming to minimize one of the most important risk factors for the diseases, a weight loss program was started and successfully executed. However, 10 months later, the dog restarted presenting neurological episodes at a high frequency (3x/week). Based on videos and the characteristics of the neurological signs, the dog was diagnosed with paroxysmal dyskinesia. To investigate the role of gluten intake on this patient's neurological signs, a dietary trial with a commercial hypoallergenic diet (gluten-free; hydrolyzed protein) was followed. During the 3 months of the dietary trial, four neurologic episodes related to food indiscretion occurred. Upon the decrease in neurological episodes, the anti-seizure drugs were slowly discontinued. During this period, the dog presented only two neurologic episodes that were related to the days that the anti-seizure drugs were decreased. For 4 months the dog remained episode-free. However, a change in the dog's diet to another gluten-free diet (higher fat) led the dog to vomit and experience another neurologic episode. Once the dog was back to the previous gluten-free diet, it clinically improved, and no other clinical signs were reported by the client during the next 5 months. Conclusion Although a relationship between gluten and paroxysmal dyskinesia cannot be confirmed, the dog's improvement after the nutritional management and the removal of the anti-seizure therapy is supportive of dietary association.